Adenovirus DNA replication facilitates binding of the MLTF/USF transcription factor to the viral major late promoter within infected cells. - Toth, M (1992)
The activity of the adenovirus major late promoter is substantially increased as the infection proceeds from the early to late phase. To gain insight into the regulation of this promoter, we analyzed protein-DNA interactions by in vivo DMS and DNasel footprinting during the course of adenovirus infection. Little or no protein interaction at promoter sequences was detected early (5 hr) after infection but strong interactions at the major late transcription factor (MLTF/USF) binding site and at the TATA box were evident late (12 hr) after infection. Comparison of in vivo and in vitro footprints revealed that the in vivo interaction late after infection results from binding of the cellular transcription factor MLTF/USF. Nuclear extracts prepared from uninfected cells as well as cells harvested at 5 and 12 hr after infection contained similar levels of MLTF/USF footprint activity, therefore the lack of a detectable interaction early after infection is not due to reduced levels of the factor early in the viral growth cycle. Viral DNA replication was required for MLTF/USF binding at the major late promoter. These results indicate that DNA replication participates in the regulation of adenovirus late gene expression by facilitating the binding of a transcription factor to the major late promoter.